Adam Smith and the character of virtue - Hanley, Ryan Patrick 1974- (Cambridge University Press, 2009)
Recent years have witnessed a renewed debate over the costs at which the benefits of free markets have been bought. This book revisits the moral and political philosophy of Adam Smith, capitalism's founding father, to recover his understanding of the morals of the market age. In so doing it illuminates a crucial albeit overlooked side of Smith's project: his diagnosis of the ethical ills of commercial societies and the remedy he advanced to cure them. Focusing on Smith's analysis of the psychological and social ills endemic to commercial society - anxiety and restlessness, inauthenticity and mediocrity, alienation and individualism - it argues that Smith sought to combat corruption by cultivating the virtues of prudence, magnanimity and beneficence. The result constitutes a new morality for modernity, at once a synthesis of commercial, classical and Christian virtues and a normative response to one of the most pressing political problems of Smith's day and ours